Jurisdição extraterritorial nos órgãos internacionais e regionais de direitos humanos: critérios, tendências e contribuições - Fernanda Menezes dos Santos (2023)
As a widely discussed topic today, extraterritorial jurisdiction has become a difficult issue for regional courts and international human rights bodies. Different criteria to define whether or not the State exercises jurisdiction outside its territory have been used, revealing the need to analyze how these institutions have interpreted extraterritorial jurisdiction in recent years. The present work aims to analyze the trend of the interpretation of regional Courts and international bodies regarding extraterritorial jurisdiction in human rights. The analysis is based on the criteria for the application of extraterritorial jurisdiction, with special focus on the European Court of Human Rights, the Inter-American Court of Human Rights and the UN Committee on the Rights of the Child. A legal-exploratory methodology will be used, with multiple case studies, through documentary and bibliographic analysis. The hypothesis is that the Courts and international bodies have their own trends, which are in line, with the exception of the European Court. At the end of the work, the hypothesis will be verified, highlighting the more extensive interpretation of the Inter-American Court and the Committee on the Rights of the Child, unlike the European Court, which remains distant, applying more restrictive positions.